Activity coefficient and solubility of amino acids in water by the modified Wilson model - Xin, Xu (2010)
The modified Wilson model for the phase behavior of polymer aqueous solutions has been applied to calculate activity coefficients and the solubility of amino acids and small peptides in aqueous solutions. The interaction parameters estimated from the activity coefficients and the solubility data are used to evaluate the solubility of amino acids. The model can accurately represent the activity coefficients of amino acids with only two adjustable parameters per system. It is also used to describe the solubility of several amino acids with satisfactory results. After introduction of the influence of temperature on the energy parameters, it is possible to obtain better predictions of the solubility at higher temperatures than those from UNIFAC and UNIQUAC. The results achieved for the solubility of a mixture of two amino acids are in good agreement with the literature data.